DISSECTING NADIEM ANWAR MAKARIM’S SPEECH AT THE SINGAPORE SUMMIT 2020: A STUDY ON ASSERTIVE SPEECH ACTS - Fantasiya Nurul Huda; Tri Septa Nurhantoro; Galant Nanta Adhitya (JOLALI: Journal of Language and Literature, 2023)
This research analyzes Nadiem Anwar Makarim’s speech at the Singapore Summit 2020, aiming to distinguish the types of assertive speech acts and to comprehend their functions with the focus on the context. This research employs descriptive quasi or mixed-method. The qualitative method is used to explain the data, while the quantitative method is used to count the percentage of the data. The findings show that there are 139 assertive utterances used by Makarim. The analysis shows that there are five types of assertive speech act found. They are 28 of 20,14% of stating, 22 of 15,82% of claiming, 54 of 38,84% of reporting, 14 or 10,07% of reminding, and 21 or 15,10% of suggesting. Each type has its function. Reporting is to give information to the hearers, stating is to commit the hearers about the fact and truth, claiming is to say that something is true when some people may say that it is not true, suggesting is to give an opinion to the hearers, and reminding is to remind the hearers not to forget the condition. It is because the way Makarim delivered his speech refers to politeness. After reading this research, it is expected that the readers can realize the language phenomenon, especially speech acts and assertive types in a speech which eventually improves the understanding of filtering an utterance.